Los estereotipos en la violencia de género en los escenarios deportivos con respecto a las Árbitras Profesionales de Fútbol del Ecuador - Lascano Núñez, Duvi Andrés (2024)
This article addresses the persistence of macho stereotypes in Ecuadorian football, particularly concerning female refereeing. Despite progress in the inclusion of women in this sport, they face ingrained challenges in gender perceptions. Society still condemns those who challenge the status quo, making it difficult for women to develop in this environment dominated by gender stereotypes and patriarchal structures, which impact violence and the development of matches directed by female referees. A qualitative methodology was employed, conducting in-depth interviews with 18 professional female referees from the country, aiming to explore the influence of gender stereotypes on their work. The results highlight the prevalence of stereotypes and economic and professional inequalities. Despite the discussed biological limitations, the importance of gender diversity in refereeing is emphasized, promoting equal opportunities and enriching the sport's perspective. Nevertheless, female referees face resistance and discrimination, manifested in unequal salaries and underestimation of their work. Therefore, there is a need to challenge ingrained stereotypes and create inclusive environments to ensure the recognition and appreciation of the work of female referees, sending a message of empowerment and equity for future generations. This study underscores the complexity of the female referees' experience in a sexist and patriarchal environment, emphasizing the urgency of addressing these issues to promote gender equality in football and society at large.